Greenland Interannual Ice Mass Variations Detected by GRACE Time‐Variable Gravity - Li, Zhen; Chao, Benjamin Fong; Zhang, Zizhan; Jiang, Liming; Wang, Hansheng (Geophysical research letters, 2022)
To better understand the impact of climate forcing on Greenland ice sheet (GrIS), we study the GrIS mass variations on the interannual timescale as observed by the satellite mission of Gravity Recovery and Climate Experiment (GRACE). By employing the method of empirical orthogonal function) analysis, we find: (a) That the GrIS interannual mass variations are significantly correlated with the Pacific Decadal Oscillation, suggesting a connection to the changes of the Icelandic Low (a permanent low‐pressure system) related to PDO; (b) An East‐West Costal Dipole related to precipitation anomaly subjects to the North Atlantic Oscillation; (c) Certain contribution of the Atlantic Multidecadal Oscillation to GrIS mass variations in the form of temperature and runoff anomalies. Plain Language Summary For the past few decades, Greenland ice sheet (GrIS) has undergone accelerated melting under impacts of the global climate changes, leading to significant change in the sea level. GrIS has been well monitored by the Gravity Recovery and Climate Experiment (GRACE) satellite mission that observes Earth's gravity change due to mass transports since its launch in 2002. Here we use GRACE data to understand the responses of GrIS to climatic forcing, which can reveal certain phenomena that are hitherto unreported: (a) We show that the Pacific Decadal Oscillation plays a significant role on GrIS variations; (b) We also report a “seesaw” pattern of an East‐West Costal Dipole related to the North Atlantic Oscillation; (c) The Atlantic Multidecadal Oscillation also contributes to GrIS mass variations. Key Points Greenland interannual mass variations are correlated with the Pacific Decadal Oscillation We report an East‐West Coastal Dipole related to the North Atlantic Oscillation The contribution of the Atlantic Multidecadal Oscillation is also captured